The Middle Stone Age occupations of Tiémassas, coastal West Africa, between 62 and 25 thousand years ago. (December 2020) - Niang, Khady; Blinkhorn, James; Ndiaye, Matar; Bateman, Mark; Seck, Birame; Sawaré, Gora
Highlights: Results of new excavations of MSA site on West African coast at Tiémassas. Three occupations at the site date between 62 and 25 thousand years ago. Lithic assemblages from each occupation share a common technological character. These provided the largest, dated assemblages to characterise MSA technology in West Africa. The results indicate long-term behavioural continuity and engagement with the West African coastline. Abstract: Chronometrically dated Pleistocene records of human occupations of West Africa are rare but offer critical information with which to explore patterns of human origins and adaptation both within the region and more widely across the continent. A number of Middle Stone Age sites are known from the larger river valleys of West Africa, but recent work at the site of Tiémassas has highlighted the presence of Late Pleistocene occupations of the West African coastline. Tiémassas is the westernmost Middle Stone Age site known from Africa, and is located at the interface of Sudanian savannahs, Guinean forest-savannah mosaics and mangrove habitats. Research in the 20th century identified rich collections of MSA stone tools at the site, and our earlier excavations at Tiémassas have constrained an occupation to ca. 44 thousand years ago. Here, we present the results of further chronological dating and detailed analyses of lithic assemblages from new excavations at the site. We synthesize these new findings with the wider suite of evidence from the site to characterize MSA occupations of the West African coast to between 62 and 25 thousand years ago. Our results suggest considerable technological continuity in stone tool technologies at Tiémassas. Despite the immediate proximity of the coastline, there is little evidence at present to suggest direct engagement with coastal resources by MSA populations. Rather, the ecotonal position of the site, alongside more diffuse benefits of its coastal position, may have provided an attractive context for Middle Stone Age occupation.